Endogamia em rebanhos de caprinos da raça Saanen - Paiva, Renato Diógenes Macedo (Universidade Federal Rural do Semi-Árido, 2016)
The Saanen goat breed is present in all countries that have a fairly developed dairy goat and the predominant race in farms and with higher milk production average. The objective of this study was to evaluate the population structure and the effect of inbreeding on the production of milk up to 305 days of lactation and duration of lactation in Saanen goats belonging to participating flocks of Breeding Program of Dairy Goats (Capragene®). The evaluated population parameters were the effective number of founders (fe) and ancestors (fa), effective size (Ne), inbreeding coefficient (F), individual increase in inbreeding (ΔFi), average coefficient of relatedness (AR), the integrity of pedigrees and Wright's F statistics. The effect of inbreeding was verified by t test evaluating contrast through a subroutine MTDFREML application. We used pedigree data from 7,640 animals and 3,548 lactation information pertaining to 2,154 goats. The mean AR and F coefficients of the population were 1.48% and 0.78%, respectively. But the effective size was 39,69, from complete equivalent generation. The effective number of founder animals (fe) and ancestors (fa) was 123 and 101 respectively, and fiam all ancestors only 39 were responsible for explaining 50% of the genetic variability within the population, which indicates loss of source genes. As for the integrity of pedigrees were identified 80.13% animals as sires (breeders) and 79.02% as mothers. For subdivision of the population of the values obtained for FIS, FST and FIT were -0.017, 0.028 and 0.011 respectively, indicating the absence of the population structuring. There was no significant effect of inbreeding on the duration of lactation (P>0.05). The production of milk up to 305 days of lactation was significantly affected by inbreeding, with a reduction of 2.31 kg with the increase of 1% in the individual inbreeding
Inbreeding in herds of Saanen breed goats
Keywords: Caprinos; Consanguinidade; Depressão endogâmica; Estrutura populacional; Goats; Inbreeding; Inbreeding depression; Population structure; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL